A loop involving NRF2, miR‐29b‐1‐5p and AKT, regulates cell fate of MDA‐MB‐231 triple‐negative breast cancer cells. Issue 2 (10th July 2019) - De Blasio, Anna; Di Fiore, Riccardo; Pratelli, Giovanni; Drago‐Ferrante, Rosa; Saliba, Christian; Baldacchino, Shawn; Grech, Godfrey; Scerri, Christian; Vento, Renza; Tesoriere, Giovanni
Abstract: The present study shows that nuclear factor erythroid 2‐related factor 2 (NRF2) and miR‐29b‐1‐5p are two opposite forces which could regulate the fate of MDA‐MB‐231 cells, the most studied triple‐negative breast cancer (TNBC) cell line. We show that NRF2 activation stimulates cell growth and markedly reduces reactive oxygen species (ROS) generation, whereas miR‐29b‐1‐5p overexpression increases ROS generation and reduces cell proliferation. Moreover, NRF2 downregulates miR‐29b‐1‐5p expression, whereas miR‐29b‐1‐5p overexpression decreases p‐AKT and p‐NRF2. Furthermore, miR‐29b‐1‐5p overexpression induces both inhibition of DNA N ‐methyltransferases ( DNMT1, DNMT3A, and DNMT3B ) expression and re‐expression of HIN1, RASSF1A and CCND2 . Conversely, NRF2 activation induces opposite effects. We also show that parthenolide, a naturally occurring small molecule, induces the expression of miR‐29b‐1‐5p which could suppress NRF2 activation via AKT inhibition. Overall, this study uncovers a novel NRF2/miR‐29b‐1‐5p/AKT regulatory loop that can regulate the fate (life/death) of MDA‐MB‐231 cells and suggests this loop as therapeutic target for TNBC. Abstract : NRF2 and miR‐29b‐1‐5p are two opposite forces, which could regulate the fate of MDA‐MB‐231 triple‐negative breast cancer (TNBC) cells. We show that NRF2 activation stimulates cell growth, whereas miR‐29b‐1‐5p overexpression reduces cell proliferation. Moreover, NRF2 downregulates miR‐29b‐1‐5p expression, whereas miR‐29b‐1‐5p overexpression decreases p‐AKT and p‐NRF2. miR‐29b‐1‐5p overexpression also induces both inhibition of DNA N ‐methyltransferases ( DNMT1, DNMT3A, and DNMT3B ) expression and re‐expression of HIN1, RASSF1A and CCND2 . Conversely, NRF2 activation induces opposite effects. This study uncovers a novel NRF2/miR‐29b‐1‐5p/AKT regulatory loop that can regulate the fate of MDA‐MB‐231 cells and suggests that compounds similar to parthenolide may be promising agents in TNBC therapy.